British and German Manufacturing Productivity Compared: A New Benchmark for 1935/36 Based on Double Deflated Value Added - Rainer Fremdling; Herman De Jong; Marcel P. Timmer (The Journal of Economic History, 2007)
We present a new estimate of Anglo-German manufacturing productivity levels for 1935/36. It is based on archival data on German manufacturing and published British census data. We calculate comparative levels of value added, correcting for differences in prices for outputs and inputs. This so-called double deflation procedure provides new insights into productivity comparisons because output- and input price structures differed greatly between the two countries. Although the new calculations confirm existing results at an aggregate level, they reveal important differences at the industry level and show how Germany was striving for autarky as it prepared its economy for war.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330